Clinical performance of the Food and Drug Administration–Approved high‐risk HPV test for the detection of high‐grade cervicovaginal lesions. Issue 5 (15th January 2016) - Zhou, Haijun; Mody, Roxanne R.; Luna, Eric; Armylagos, Donna; Xu, Jiaqiong; Schwartz, Mary R.; Mody, Dina R.; Ge, Yimin
Abstract : BACKGROUND: In recent years, high‐risk human papillomavirus (hrHPV) testing for triaging atypical squamous cells of undetermined significance and cotesting with cytology have been implemented in clinical practice. However, clinical data for primary screening with human papillomavirus (HPV) testing alone are currently lacking. METHODS: This study retrospectively reviewed the correlation of cytology, histology, and hrHPV testing through the use of a cytology laboratory quality assurance database with 130, 648 Papanicolaou (Pap) tests interpreted at Houston BioReference Laboratories and Houston Methodist Hospital between March 1, 2013 and June 30, 2014. Among the 47, 499 patients who had undergone cytology‐HPV cotesting, 1654 underwent follow‐up biopsies. RESULTS: The sensitivities of the hrHPV and Pap tests were 80.8% and 81.2%, respectively, for detecting any type of cervicovaginal dysplasia and 91.3% and 90.9%, respectively, for high‐grade cervicovaginal lesions. For biopsy‐confirmed high‐grade cervicovaginal lesions (cervical intraepithelial neoplasia grade 2+, adenocarcinoma in situ, or carcinoma; n = 253), the false‐negative rates for hrHPV and Pap tests were 8.7% and 9.1%, respectively. The false‐negative rate for cytology‐hrHPV cotesting was only 1.2%. CONCLUSIONS: In clinical practice, the hrHPV test alone is not significantly superior to the Pap test as a primary screening method for cervicovaginal lesions. The false‐negative rate of the hrHPV test in detecting biopsy‐confirmed high‐grade cervicovaginal lesions is comparable to the rate of the Pap test. Women with cytology and hrHPV cotesting, however, have a significantly lower false‐negative rate than those undergoing either test alone. Currently, cytology‐HPV cotesting remains the best strategy for detecting high‐grade cervicovaginal lesions. Cancer Cytopathol 2016;124:317–23 . © 2016 American Cancer Society . Abstract : In clinical practice, the high‐risk human papillomavirus test alone is not significantly superior to the Papanicolaou test as a primary screening method for cervicovaginal lesions. Cytology–human papillomavirus cotesting currently remains the best strategy for detecting high‐grade cervicovaginal lesions.